APPROACHES OF FORMATION OF STRATEGY IN THE TOURISM INDUSTRY - Marianna M. Romanova (Статистика и экономика, 2016)
In the article various approaches offormation of strategy of development ofthe enterprises and various branches ofeconomy are analyzed, stages of evolution of strategic planning are considered.The attention is concentrated on the basic factors inﬂuencing success of travel agency.